2023
DOI: 10.1021/acsami.2c22205
|View full text |Cite
|
Sign up to set email alerts
|

Toward Nonvolatile Spin–Orbit Devices: Deposition of Ferroelectric Hafnia on Monolayer Graphene/Co/HM Stacks

Abstract: While technologically challenging, the integration of ferroelectric thin films with graphene spintronics potentially allows the realization of highly efficient, electrically tunable, nonvolatile memories through control of the interfacial spin−orbit driven interaction occurring at graphene/Co interfaces deposited on heavy metal supports. Here, the integration of ferroelectric Hf 0.5 Zr 0.5 O 2 on graphene/Co/heavy metal epitaxial stacks is investigated via the implementation of several nucleation methods in at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…This annealing results in a degradation of the interface between the ferroelectric oxide and the highly reactive ferromagnetic metal grown on top of it. Lancaster et al 32 reported state-of-the-art ferroelectric properties in Hf 0.5 Zr 0.5 O 2 adjacent to a graphene/Co/heavy metal stack. Large polarization values were only obtained while using an interface oxide layer, likely at the expenses of the magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%
“…This annealing results in a degradation of the interface between the ferroelectric oxide and the highly reactive ferromagnetic metal grown on top of it. Lancaster et al 32 reported state-of-the-art ferroelectric properties in Hf 0.5 Zr 0.5 O 2 adjacent to a graphene/Co/heavy metal stack. Large polarization values were only obtained while using an interface oxide layer, likely at the expenses of the magnetoelectric coupling.…”
Section: Introductionmentioning
confidence: 99%